ERRORS IN THE USAGE OF ENGLISH PREPOSITIONS PRODUCED BY COLLEGE STUDENTS IN YOGYAKARTA - Nawangsasi, Esthi; Wijana, I Dewa Putu (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Errors are very natural and even become an important part of learning (Davies, 2000:105). Therefore, there are many scientists who analyze errors to achieve better understanding on how students learn language. Based on the importance of conducting error analysis, this research is developed to analyze errors in the usage of English prepositions as there are still limited number of people who analyze this topic. The data used are utterances produced by third year college students majoring in English. All of the students’ utterances are obtained through interview. The data obtained was then transcribed and analyzed by applying a theory of preposition stated by Collins (1991). The results show that there are 15 prepositions which are used incorrectly in the students’ untterances such as about, among, as, at, because of, by, during, for, from, in, of, on, through, to, and with.